Application of Problem Posing in Mathematics Learning Material for Building Flat Side Spaces - Febriani Corneli Fanda Languju; Ichdar Domu; Rosiah J. Pulukadang (Departement of Mathematics Education, 2024)
This research aims to determine the differences in the average learning outcomes of students taught using the Problem Posing learning model on flat-sided geometric material at Woloan Christian Middle School. This research used the experimental method on class VIII students at Woloan Christian Middle School. The samples in the study were class VIII-A as an experimental class with a total of 31 students and class VIII-B as a control class with a total of 31 students, a total of 62 students at Woloan Christian Middle School, even semester of the 2023/2024 academic year. The instrument used in this research consisted of a learning outcomes test in the form of a written test in the form of an essay with flat-sided geometric material. The technique for collecting observation and test data is in the form of evaluation questions. The test is carried out twice. Namely, the pretest is carried out at the beginning of the research to determine students' achievement scores before treatment, and the posttest is carried out on both control and experimental groups after treatment. Based on hypothesis testing using SPSS test statistics, where from the calculation results of the Tcount value of 1.822 with Ttable 1.671 (1.822>1.671), it can be said that there is a significant difference in the average learning outcomes of the experimental group using Problem posing and the control group using the learning model. Direct Instruction, which means that there is an influence of the application of the Problem posing learning model on the average learning outcomes of class VIII students at Woloan Christian Middle School